THE MIGRATION PATH OF CO IONS IN CO-SUBSTITUTED SPINEL FERRITE THIN-FILMS DURING MAGNETIC ANNEALING - NA, JG; LEE, TD; KIM, EC; KIM, CS; PARK, SJ (JAPAN J APPLIED PHYSICS, 1993)
The migration path of Co ions in Co-substituted spinel ferrite thin films is investigated in detail during magnetic annealing. To this end, changes in the saturation magnetization were measured as a function of magnetic annealing time at various temperatures. Changes in Mossbauer spectra were also taken. The ferrite thin films were prepared by a reactive sputtering method. For Co-substituted ferrite thin films annealed at various temperatures, peaks were observed in the plots of the saturation magnetization vs annealing time, whilst the saturation magnetization remained nearly constant for Co-free ferrite thin films during magnetic annealing. From a subsequent Mossbauer spectroscopic investigation, it was confirmed that the peaks in the saturation magnetization-annealing time curves for Co-substituted ferrite thin films are originated from cation redistribution, i.e., the migration of Fe ions on tetrahedral sites (A sites) to octahedral sites (B sites) and Co ions on the B sites to the A sites.